Etiology of adult onset seizures: Role of magnetic resonance imaging - Geetanjali Andani; Nagendra R Patil; Reddy, Santosh (Asian Journal of Medical Sciences, 2023)
Background: Neuroimaging is an important diagnostic tool which aids in detecting structural, vascular, neoplastic, and demyelinating causes of symptomatic seizures and may predict risk of seizure recurrence. Magnetic resonance imaging (MRI) is a sensitive neuroimaging modality which can detect subtle lesions, their exact location, and extent, which cannot be revealed by computed tomography (CT) scan. Because of its excellent soft-tissue contrast and detailed depiction of anatomy, MRI has emerged as the most valuable tool for the localization of underlying pathology. As a result, the goal of this study is to investigate the etiological factors for adult-onset seizures using MRI. Aims and Objectives: The goal of this study is to investigate the etiological factors for adult-onset seizures using MRI. Materials and Methods: The present study was an observational prospective study of 50 patients presented to the Department of Radiodiagnosis at Basaweshwar Hospital and met the inclusion criteria of the study. The inclusion criteria were to include all those cases who presented with seizures and all of them were subjected to brain MRI. The imaging findings were analyzed, described, and represented in the form of tables and charts. Results: The mean age of all patients was 44.05 years, with males being 43.63 years old and females being 44.48 years old. The generalized tonic–clonic seizures were the most common type of seizure in 59 (84.3%). The most common MRI findings were ring enhancing lesion (14%), infract with gliosis (13.6%), and neoplasm (10.3%). Conclusion: MRI was able to detect an underlying lesion causing symptomatic seizures with added advantage of no radiation exposure, and superior neuroimaging modality and should be the investigation of choice in all patients who had a history of convulsions after ruling out systemic and metabolic causes of convulsion.